INTERPRETATION OF THE CONCEPT OF NATIONAL VALUES - Olimjon Isakov (Scholar Express Journal, 2022)
National values as an integral part of spiritual heritage have been considered a powerful source of spirituality in Uzbekistan for centuries. Despite various changes, the Uzbek people have preserved their historical and cultural values and are passing them down from generation to generation. This article highlights the concept of national values
Keywords: value; national values; common values; vital values